Nanoscaled Films and Layers 2017
DOI: 10.5772/67570
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanolayer on Surface of EPD Coatings Based on Poly-Ether-Ether-Ketone

Abstract: Poly-ether-ether-ketone (PEEK) is a high performance polymer with many intrinsic properties. When it is used in the form of coating, an improvement of some of its functional properties was achieved by forming a surface nanolayer. In this chapter, it will be described how it was possible to obtain this result. Firstly, three kinds of PEEK composite coatings were deposited by electrophoretic deposition, adding alumina particles, polytetrafluoroethylene (PTFE) and lignin to PEEK. Then, the composite coatings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 35 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Two signals can be noticed in the Ca region of the B sample (Figure 7m 36), (37). The third signal is at lower binding energies usually associated to C bonds with metals, with possible presence also of oxygen, as reported in (41) for Al-O-C or in (42) for Ti-C. In the oxygen region of H+P (Figure 7g), two main contributions can be noticed at 529.94 eV and 531.46 eV and a very low signal at 532.93 eV.…”
Section: Accepted Articlesupporting
confidence: 52%
See 2 more Smart Citations
“…Two signals can be noticed in the Ca region of the B sample (Figure 7m 36), (37). The third signal is at lower binding energies usually associated to C bonds with metals, with possible presence also of oxygen, as reported in (41) for Al-O-C or in (42) for Ti-C. In the oxygen region of H+P (Figure 7g), two main contributions can be noticed at 529.94 eV and 531.46 eV and a very low signal at 532.93 eV.…”
Section: Accepted Articlesupporting
confidence: 52%
“…Finally, the high-resolution spectrum of Ca shows a shift of the peaks to lower energy for H+P and not for B+P (an opposite shift can be observed in this case). A decrease in the characteristic binding energies of the metals ions (Ca 2+ ions) has been associated to the formation of complex compounds with polyphenols (41).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…There are several works that have been carried out on the EPD of composite Al 2 O 3 /PEEK coatings. 26,27,33,34 Uniform nanocomposite alumina/PEEK coatings containing between 20 and 70 wt% of PEEK were deposited on stainless steel substrates for the first time by Corni et al 27 These important investigations showed that the deposited coatings were too rich in alumina and that a lower amount of alumina would be enough to satisfactorily increase the mechanical properties and coating adhesion to the steel substrate. Corni et al 26 have studied the effects on the deposition efficiency of EPD parameters, such as the deposition time, the difference of potential applied and their interactions, using a neural network approach to develop a quantitative understanding of the nano-size Al 2 O 3 /PEEK system.…”
mentioning
confidence: 99%
“…PEEK-alumina coating with different alumina content were also electrophoretically deposited by De Riccardis. 33 The different temperature …”
mentioning
confidence: 99%